Representation of Violence In English Children's Lullabies Lyrics (Conference on English Language Teaching, 2023)
This study examines the analysis of violence representation in several English children's lullabies such as Oranges and Lemons, Ring Around The Rosies, London Bridge is Falling Down, Rockabye Baby and Baa Baa Blacksheep by using CDA related to text, social cognition and context. The purpose of using CDA is to identify the relationship of text with social cognition and the context of English children's lullabies lyrics, in this point of view,  represents theories about reality, kinds of things and situations in the world. It uses a qualitative descriptive method through a representational approach. In the data collection, the author uses some techniques through the process of procuring primary data for research purposes of systematic and standard procedures to process data requirement through observation and documents study because the data used is transcribed via text. The results of this study will show the relationship between text, social cognition and context in the English children's lullabies lyrics, Oranges and Lemons, Ring Around The Rosies, London Bridge is Falling Down, Rockabye Baby and Baa Baa Blacksheep which may differ from society's point of view in general. This study also seeks to reveal the problems that often arise in understanding meaning.